2013
DOI: 10.1007/s11033-013-2534-2
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensinogen gene M235T polymorphism and acute myocardial infarction risk: a meta-analysis of 22 studies

Abstract: Angiotensinogen, one of the most important proteins in the renin-angiotensin system, plays a key role in the progress of coronary heart disease and myocardial infarction (MI). Many studies have investigated the association between angiotensinogen gene M235T polymorphism and MI risk, but the results were inconsistent. We performed a meta-analysis of 22 studies on M235T polymorphism and MI risk published before November 2012. This meta-analysis included a total of 4,606 MI cases and 4,918 controls. Overall, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…3 reports were excluded because the full-texts were not available ( 47 - 49 ). 3 other reports were excluded because they were meta-analyses ( 50 - 52 ). 2 studies did not have accessible original data ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 reports were excluded because the full-texts were not available ( 47 - 49 ). 3 other reports were excluded because they were meta-analyses ( 50 - 52 ). 2 studies did not have accessible original data ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sui and Gao ( 50 ) reported no association between AGT -M235T and the MI risk, even in the subgroup analysis comprising different ethnic and control sources. However, they ( 50 ) included incorrect alleles and genotypes frequencies from 8 studies ( 29 - 32 , 36 , 39 , 40 , 43 ). Liang et al ( 51 ) and Wang and Pan ( 52 ) found an association between the polymorphism and MI risk in Asian population only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Влияние М235Т полиморфизмов гена AGT на риск развития ССЗ в различных этнических группах отра-жено в трех крупных мета-анализах (Liang X, et al, 2013, Sui X, et al, 2013, Wang YI, et al, 2014, прове-денных независимыми авторами в период с 2013 по 2014гг. На основе 75 работ, включавших 28109 жителей Юго-Восточной Азии с подтвержденными БСК установлено, что Т235Т генотип повышает риск развития инфаркта миокарда примерно в 3 раза чаще, чем дикий М235М вариант.…”
Section: таблицаunclassified
“…На основе 75 работ, включавших 28109 жителей Юго-Восточной Азии с подтвержденными БСК установлено, что Т235Т генотип повышает риск развития инфаркта миокарда примерно в 3 раза чаще, чем дикий М235М вариант. В случае с европейцами эта закономерность не прослеживается [8][9][10].…”
Section: таблицаunclassified